Implikasi Keputusan Tata Usaha Negara Persetujuan Peningkatan Produksi Kontrak Karya dalam Penegakan Keadilan pada Peradilan Tata Usaha Negara - Mohamad Rizki Irmansyah; Didik Suhariyanto; Dewi Iryani (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Environmental pollution occurs when the cycle of matter in the living environment changes so that the balance in terms of structure and function is disturbed. Imbalances in the structure and function of the material cycle occur due to natural processes or also due to human actions. In this modern age, there are many human activities or actions to fulfill biological needs and technological needs, thus causing a lot of environmental pollution. If there is a problem regarding environmental destruction or damage to the environment, it is almost certain that human activity is the main cause. The research method used is the Normative Juridical research type, in accordance with the objectives the author wants to achieve, the methodology in designing the thesis research uses two types of approaches, namely the Statutory Approach and the Conceptual Approach. The Statute Approach is an approach carried out by examining all laws with the concept of law. The implications of the state administration's decision to approve increased production of work contracts, provisions containing the principle of absolute responsibility, cannot yet be implemented, considering that Article 21 of Law No. 23 of 1997 concerning Environmental Management with implementing regulations that have not been made has resulted in lawsuits in environmental cases. in courts requesting the application of the principle of absolute responsibility is often not accepted. Enforcement of environmental law through civil procedures is regulated in Chapter either based on an agreement between the parties or using the services of a mediator and/or arbitrator. A lawsuit via litigation (court action) can only be pursued if efforts to resolve the dispute outside of court are unsuccessful.